Evaluation of district mental healthcare plans: the PRIME consortium methodology - De Silva, Mary J. (Br J Psychiatry, 2016)
Background Few studies have evaluated the implementation and impact of real-world mental health programmes delivered at scale in low-resource settings. Aims To describe the cross-country research methods used to evaluate district-level mental healthcare plans (MHCPs) in Ethiopia, India, Nepal, South Africa and Uganda. Method Multidisciplinary methods conducted at community, health facility and district levels, embedded within a theory of change. Results The following designs are employed to evaluate the MHCPs: (a) repeat community-based cross-sectional surveys to measure change in population-level contact coverage; (b) repeat facility-based surveys to assess change in detection of disorders; (c) disorder-specific cohorts to assess the effect on patient outcomes; and (d) multilevel case studies to evaluate the process of implementation. Conclusions To evaluate whether and how a health-system-level intervention is effective, multidisciplinary research methods are required at different population levels. Although challenging, such methods may be replicated across diverse settings.